What dialogue after Gaza? - Cheyette, Bryan (Patterns of prejudice, 2025)
The fifth war in Gaza this century is, at the time of writing, two years old with a massive loss of civilian life, including 20,000 children, and the obliteration of most of Gaza's infrastructure. Specialists in Genocide Studies have described it as a 'genocide'. We can only hope that, by the time this Commentary is published, the ceasefire will continue to hold and be followed by a comprehensive peace plan including Palestinian national rights. The violence was precipitated by the Hamas-instigated massacre of 1,200 Israelis and foreign nationals, mainly civilian, and the capture of 251 hostages. What dialogue is possible after such mutual bloodletting? Cheyette follows Edward Said, the Palestinian scholar activist, who believed that discussion and dialogue are of the highest moral order in Israel/Palestine and, more realistically today, within the academy where he worked. Is the Israel/Palestine conflict a tragedy, as Said argued, which can only be ended by the political and ethical necessity of discussion and dialogue? Or is it a settler-colonial crime that denigrates discussion and dialogue as a means of normalizing the criminal? How can we effect change as thinking activists and not add to the hostility? Cheyette engages with both the memory of the Holocaust and the ongoing Nakba in a bid to engage with these questions.